Pradofloxacin Minimum Inhibitory Concentration Profiling of Streptococcus suis Isolates: Insights into Antimicrobial Susceptibility in Swine - Jessica Risser; Ronald Tessman; Don Bade; Orhan Sahin; Maria J. Clavijo; Saumya Dhup; Patrick Hoffmann (Pathogens)
This study evaluated the minimum inhibitory concentration (MIC) of pradofloxacin against various swine respiratory pathogens, including Bordetella bronchiseptica, Glaesserella parasuis, Mycoplasma hyopneumoniae, Pasteurella multocida, and Streptococcus suis (S. suis), associated with disease in swine. This research was conducted in two phases: the initial phase examined isolates from the lungs that could be either commensal or pathogenic, while the second phase focused on systemic S. suis strains that spread from the respiratory tract to the brain. The pradofloxacin MIC values of the second phase were within the MIC range of the initial phase, with MIC50 and MIC90 values highlighting its potential as an effective antimicrobial agent. Quality control data validated the reliability of our MIC findings, with all pradofloxacin MIC values for control organisms within approved ranges. These findings suggest that pradofloxacin has broad-spectrum activity against Gram-positive and Gram-negative bacteria and may serve as a reliable therapeutic option for managing S. suis and other swine respiratory infections. This study highlights pradofloxacin as an alternative antimicrobial therapy for swine respiratory diseases, offering a potential solution amidst rising concerns over antibiotic resistance.